Human African Trypanosomiasis (sleeping sickness): Current knowledge and future challenges - Papagni, Roberta; Novara, Roberta; Minardi, Maria Letizia; Frallonardo, Luisa; Panico, Gianfranco Giorgio; Pallara, Elisabetta; Cotugno, Sergio; Ascoli Bartoli, Tommaso; Guido, Giacomo; De Vita, Elda; Ricciardi, Aurelia; Totaro, Valentina; et al. (Frontiers in Tropical Diseases, 2023)
According to both definitions of US Centers for Disease Control and Prevention and World Health Organization, Neglected Tropical Diseases (NTDs) are a group of preventable and treatable parasitic, viral, and bacterial diseases that affect more than one billion people globally. They generally afflict the more indigent patients of the world and historically have not received as much attention as other diseases. NTDs tend to thrive in low-income regions, where water quality, sanitation and access to health care are substandard. They are common in several countries of Africa, Asia, and Latin America. In this literature review, we want to focus on Human African Trypanosomiasis (HAT), also known as “sleeping sickness”, one of the most common neglected diseases in Africa. It is caused by infection with the subspecies of the parasitic protozoan Trypanosoma brucei, and it is transmitted by the bite of the tsetse fly. It puts 70 million people at risk throughout sub-Saharan Africa and it is usually fatal if untreated or inadequately treated. This review covers several aspects of the disease. We focused our interests on most recent epidemiological data, novel diagnostic methods with their advantages and limitations, new improved treatment and orphan drugs and eradication programs, including vector control, according to a “One Health” approach, to achieve the new goals recently set by WHO.